Role of extracorporeal shockwave therapy and injectable corticosteroids in the treatment of lateral epicondylitis: a comparative study of 100 patients - Sharma, Yogesh; Philip, Vivek Mathew; Joshi, Gururaj R.; BM., Naveen BM. (International Journal of Research in Medical Sciences, 2016)
Background: Even though considered to be self-limiting, lateral epicondylitis (tennis elbow) can cause significant impediment in professional and activities of daily living. A safe and minimally invasive procedure that will enable patients to return to their daily activities as soon as possible should be advocated in the management of this condition. The aim of the present study was to investigate the role of extracorporeal shock wave therapy (ESWT) and injectable corticosteroids in the treatment of lateral epicondylitis with the secondary objective of comparing the difference in pain relief and functional improvement in patients treated with both modalities. Methods: A cross sectional analytical study was conducted over an 18 month period.100 patients were randomized into two groups, A (51 patients) who received three sessions of ESWT on weekly intervals and B (49 patients) who received two intra-lesional injections of 1ml of methylprednisolone and 2% lignocaine on weekly intervals. The patients were followed up at 3 weeks, 6 weeks and 6 months after the interventions. Subjective and objective improvements were measured using visual analogue score (VAS) and Patient Rated Tennis Elbow Evaluation Score (PRTEE). Results: The mean VAS in both groups reduced from 8.47 and 8.53 to 2.51 and 1.67 respectively at the end of the follow up (p <0.001) .The mean PRTEE score in Group A reduced from 80.59 to 26.53 (p<0.001) and Group B from 82.76 to 13.59 (p<0.05). In Group A (ESWT), the average reduction In PRTEE Score at the end of follow up was 54.06 and Group B (steroids) was 69.16. The difference was found to be statistically significant (p<0.001) favouring steroid injections. Conclusions: Both ESWT and steroid injections were found to be effective in producing symptomatic pain relief and improving the functional disability in the management of lateral epicondylitis. The comparison of both modalities showed a statistically significant improvement in pain and functional disability in favour of steroids at a short duration of follow up i.e., 03 weeks, 06 weeks and 06 months.